The influence of education on tax avoidance and tax evasion - Kassipillai, Jeyapalan; Aripin, Norhani; Amran, Noor Afza (Atax, The University of New South Wales, 2003)
This study evaluates the influence of education on tax compliance among undergraduate students in Malaysia.The survey considers existing literature in the field of education and ascertains whether education can influence the respondents’ compliance behaviour. The statistical findings confirm the prevalence of a relationship between education and tax compliance.This relationship is generally consistent, particularly so to the questions relating to general avoidance and personal avoidance. There is an improvement in personal tax compliance among students especially among females after one semester of pursuing a preliminary taxation course.It is suggested that universities providing courses in social science as well as business, management and accounting studies should offer the preliminary taxation course as a core subject to all their students.